Webinars in higher education - Mohorovičić, Sanja; Strčić, Vedran; Lasić-Lazić, Jadranka (2011)
The application of information technologies in higher education has the unquestionable potential to increase the quality of teaching and efficiency of learning. This paper researches different aspects and features of webinars, which could be used in higher education as one of many online tools in blended learning. Webinar preparation and conduction aspects are investigated and technical requirements are stressed, along with possible problems during implementation. The research results, obtained by questionnaires comprising of student opinions and their readiness for webinar usage, are presented.
Projekt MZOS
Projekt MZOS
ENG